Flipons - Herbert, Alan (Taylor & Francis, 2024)
Alan Herbert has played a leading part in discovering the biological roles for a high-energy form of DNA twisted to the left rather than to the right. Both Z-DNA and the Z-RNA sensing proteins are critical for protecting hosts against both viruses and cancers. The proteins also play critical roles in the programmed cell death of aging cells. Other types of flipons exist and alter the readout of transcripts from the genome, encoding genetic information by their shape rather than by their sequence. Many of these flipons are within repeat elements that were previously considered to be just genomic junk. Instead these genetic elements increase the adaptability of cells by flipping DNA conformation. By acting as digital switches, the different flipon types can alter cellular responses without any change to their sequence or any damage to DNA. These highly dynamic structures enable the rapid evolution of multicellular organisms. The junk DNA in repeats also encode peptide patches that enable the assembly of cellular machines. The intransitive logic involved enhances the chance of an individual surviving a constantly changing environment.